Book Publishing and Its Fundamentals as a Parameter for Socio-Economic Development in Nigeria: a Comparative Appraisal - Ajayi, Olayemi T.; Ihebuzor, Lambert. A. (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2023)
This study delves into the paramount role of book publishing in steering Nigeria’s socio-economic development. It highlights the far-reaching impacts, encompassing cultural diffusion, financial empowerment, job creation, and global information dissemination. The study underscores the vulnerability of societies lacking quality books, leading to economic instability and skill deficits. By comparing global publisher numbers and situating Nigeria’s meager 31 indigenous publishers against a potential 2,712, the disparity becomes glaring. Employing a comparative appraisal methodology with a blend of primary and secondary data sources, the research illuminates the transformative journey of book publishing. The study advocates for substantial investments from government bodies, NGOs, and corporate entities to amplify the circulation of knowledge. The implications resonate with the urgent need for strategic interventions to bolster the dissemination of quality information, thereby fostering national development and addressing the challenges posed by a burgeoning population in Nigeria